Understanding of Islamic Working Capital among MSMEs and Its Impact on Micro-Business Growth (Case Study of Muaro Jambi MSMEs) - Muhamad Rasyid Rahmatullah; A. Yuli Tauvani; Salmia; Mohd. Haramen; Ahabbi Rahman; Lisda Ariany (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to examine the level of understanding of Islamic working capital among Micro, Small, and Medium Enterprises (MSMEs) and to analyze its impact on the growth of micro-businesses in Muaro Jambi Regency. Islamic working capital refers to the management of short-term business finances based on Sharia principles, emphasizing fairness, transparency, risk sharing, and the prohibition of interest-based transactions. A quantitative research approach with a case study design was employed. Data were collected through structured questionnaires distributed to MSME owners selected using purposive sampling. The variables measured included the understanding of Islamic working capital as the independent variable and micro-business growth as the dependent variable. The collected data were analyzed using descriptive statistics and simple linear regression with the assistance of SPSS version 27. The findings indicate that MSME owners generally demonstrate a moderate level of understanding of Islamic working capital, with stronger knowledge observed among entrepreneurs who have participated in financial literacy programs or utilized Islamic financial services. Furthermore, the study reveals that understanding Islamic working capital has a positive and significant effect on micro-business growth by improving financial management practices, enhancing access to Sharia-compliant financing, strengthening business resilience, and promoting sustainable business development. Entrepreneurs with greater Islamic financial literacy tend to manage working capital more efficiently, make better financial decisions, and achieve higher levels of business performance. These findings highlight the importance of strengthening Islamic financial literacy through collaborative efforts involving government institutions, Islamic financial institutions, universities, and MSME development agencies. The study contributes to the literature on Islamic financial management by providing empirical evidence that understanding Islamic working capital is an important strategic factor in supporting the sustainable growth of MSMEs and promoting inclusive economic development in Indonesia.